2020
DOI: 10.1590/1806-9282.66.s1.82
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced nephrotoxicity

Abstract: SUMMARY Acute kidney injury is a very common diagnosis, present in up to 60% of critical patients, and its third main cause is drug toxicity. Nephrotoxicity can be defined as any renal injury caused directly or indirectly by medications, with acute renal failure, tubulopathies, and glomerulopathies as common clinical presentations. Some examples of drugs commonly associated with the acute reduction of glomerular filtration rate are anti-inflammatories, antibiotics, such as vancomycin and aminoglycosides, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 18 publications
(1 reference statement)
2
49
0
15
Order By: Relevance
“…Drug-induced AKI accounts for up to 60% of all cases, resulting in a severe threat to hospitalized patients [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-induced AKI accounts for up to 60% of all cases, resulting in a severe threat to hospitalized patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced AKI accounts for up to 60% of all cases, resulting in a severe threat to hospitalized patients [ 4 ]. Cisplatin is one of the most efficient and widely used antineoplastic drugs; however, its application is restricted due to the side effects, including nephrotoxicity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…D-AKI was found to be associated with 46 drugs, and the incidence was calculated, significantly improving the efficacy in determining the ADR occurrence in a large sample population in a multidrug environment. Currently, AKI is still a common complication that is associated with a high mortality rate and prolonged hospital stay [ 26 , 27 ]. Accordingly, studying D-AKI to determine specific risk factors is of major importance.…”
Section: Discussionmentioning
confidence: 99%
“…Safety of psychotropic drugs is nowadays one of the most ambiguous research problems. Concerns regarding the possible detrimental effect of psychotropic medications on kidney function are supported by a recent meta-analysis [3], [4]. Recently, several independent researchers have reported that psychotropic remedies exhibit a cytotoxic effect in human cell cultures, increasing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of nephrotoxicity is induced by drugs [2], [3]. Medicinal lesions of the kidneys are one of the common causes of both acute and chronic nephropathy, endangering the patient's life.…”
Section: Introductionmentioning
confidence: 99%